A closed universe: de Sitter cosmic gate - Forghani, S. Danial; Mazharimousavi, S. Habib (Elsevier, 2022)
A new cosmological object in analogy with the concept of a wormhole in general relativity is introduced. As wormholes connect two distant points through a tunnel in spacetime, this new object connects two spacetime through a large mouth which is referred to as a Cosmic Gate . In this context, two identical copies of the regular part of the de Sitter spacetime are cut through a timelike hyperplane. Then, they are glued at their identical boundaries (the only boundary) to form a complete spacetime. The stability of the cosmic gate against a linear radial perturbation is studied as well. Finally, the radial geodesics of the spacetime for a timelike and a null particle are presented. (c) 2022 The Author(s). Published by Elsevier B.V. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/).
Keywords: Thin-Shell Wormholes; Linearized Stability